Assessing the Need for Imaging after Distal Radius Fracture Fixation - Jain, Nirbhay S.; Barr, Meaghan L.; Pflibsen, Lacey R.; Benhaim, Prosper (Journal of Wrist Surgery, 2024)
Distal radius fractures are extremely common. Patients routinely undergo early imaging (around 2 weeks) after open reduction and internal fixation (ORIF) of distal radius fractures despite no clinical concerns. We analyzed the need for these radiographs by evaluating when imaging identifies complications after surgery.All distal radius fractures treated with ORIF via a volar approach by the senior surgeon were included. Intraoperative and postoperative images were analyzed for maintenance of reduction and complications. Demographic data, fracture characteristics, and postoperative complications were also recorded.A total of 342 patients were identified. Postoperative images were obtained from 0 to 14, 15 to 90, 91 to 180, 181 to 365, or greater than 365 days after surgery. Some patients had multiple images. Measurements on postoperative images were statistically equivalent across all time points. Complications mostly occurred >90 days after surgery. Of the 26 patients with complications, 5 had a failure of reduction or plating seen on postoperative imaging. Two occurred after unrelated trauma; only three patients had unanticipated complications caught on routine imaging within 3 months after surgery. These patients had extraordinarily complex fractures in poor bone stock.Early postoperative imaging is not necessary after ORIF for distal radius fractures unless the patient is elderly, or the fracture is severely comminuted with ulnar column or die-punch components. Thus, we suggest that patients have imaging only in the 3- to 6-month period to determine if the union has been achieved, which could provide cost savings to both surgeon and patient.
Keywords: distal radius; postoperative management; imaging